175 Flow Cytometry As an Adjunct in the Diagnosis of Cutaneous Lymphoma: A Case of T-Cell Rich Cutaneous Marginal Zone Lymphoma Masquerading as Pseudolymphoma. (11th January 2018) - McEwen, Abbye; Soma, Lorinda; Robin, Adam
Abstract: Distinguishing neoplastic from reactive cutaneous lymphoid infiltrates remains a diagnostic challenge. While flow cytometry is broadly used in hematopathology, it is only now emerging as a method for determining the immunophenotype and clonality of cutaneous lymphocyte populations. Cutaneous marginal zone lymphomas are particularly challenging; these cases often have lymphoid follicles with reactive features, and the neoplastic cells can be greatly outnumbered by the associated reactive, polyclonal B- and T-lymphocyte populations. We present the case of a 53-year-old man who presented with a three-year history of a patch on the left cheek. Two biopsies, taken a year apart, showed a dense nodular superficial and deep perivascular, perifollicular, and peri-eccrine mixed lymphoid infiltrate (60% B-cells and 40% T-cells), composed mainly of small lymphocytes with focal reactive germinal centers. These findings were initially interpreted as being most consistent with a reactive process, or pseudolymphoma. Because the lesion failed to regress after multiple steroid injections, a third biopsy was taken. Although this specimen had similar morphologic features, flow cytometry was performed and revealed a small abnormal B-cell population comprising 1.14% of total white blood cells. These B-cells showed abnormal expression of CD11c and were lambda light chain restricted with normal expression of CD19, CD20, CD38, and CD45 without CD5, CD10, or CD43. In addition, a small lambda light chain restricted plasma cell population was identified (0.01% of total white blood cells). No abnormal T-cells were identified. Molecular studies confirmed the presence of a clonal immunoglobulin gene rearrangement. Taken together, these findings were interpreted as cutaneous marginal zone lymphoma; the patient was then referred to oncology for staging and further management. The case underscores the limitations of morphology and immunohistochemistry alone in the diagnosis of cutaneous lymphomas and demonstrates the sensitivity of flow cytometry in detecting small, abnormal lymphocyte populations that might otherwise be overlooked.